2011
DOI: 10.1159/000328999
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical Paracicatricial Cutaneous Satellitosis of Giant Cell Tumour of the Tendon Sheath, Localized Type

Abstract: Tenosynovial giant cell tumour (localized type) is a tumour of tendon sheaths and interphalangeal joints, affecting the digits and arising from the synovium. It is characterized by a proliferation of mononuclear cells and osteoclast-like polykaryocytes. Its propagation to the skin is an exceptional event, which can take place either in localized form in the fingertips (localized type) or in the rare diffuse form called giant cell tumour of the tendon sheath (diffuse type). We report here a case of giant cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was found that the disease occurs more frequently in middle-aged women compared with men (4). According to the position (large or facet joint; intra-or extra-articular), characteristics (benign or malignant) and growth pattern (diffuse or localized) of the tumor, GCTS may be classified as one of four types: Localized-type tenosynovial giant cell tumor (L-GCTS); diffuse-type tenosynovial giant cell tumor (D-GCTS); pigmented villonodular synovitis (PVNS) (5,6); and malignant tenosynovial giant cell tumor (M-GCTS) (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the disease occurs more frequently in middle-aged women compared with men (4). According to the position (large or facet joint; intra-or extra-articular), characteristics (benign or malignant) and growth pattern (diffuse or localized) of the tumor, GCTS may be classified as one of four types: Localized-type tenosynovial giant cell tumor (L-GCTS); diffuse-type tenosynovial giant cell tumor (D-GCTS); pigmented villonodular synovitis (PVNS) (5,6); and malignant tenosynovial giant cell tumor (M-GCTS) (7,8).…”
Section: Introductionmentioning
confidence: 99%